Plasma levels of soluble receptor for advanced glycation end products in Alzheimer's disease. (4th May 2017) - Xu, Xiao-Yan; Deng, Chang-Qing; Wang, Jian; Deng, Xiao-Juan; Xiao, Qian; Li, Yuan; He, Qi; Fan, Wen-Hui; Quan, Feng-Ying; Zhu, Yao-Ping; Cheng, Ping; Chen, Guo-Jun
Abstract : Background : A decreased plasma level of soluble form of the receptor for advanced glycation end products (sRAGE) in patients with Alzheimer's disease (AD) has been reported. However, no evidence has shown whether the sRAGE plasma level of AD patients may differentiate from other types of dementia. Methods : Our study assessed sRAGE concentrations in the following 121 individuals in Chongqing area: 36 patients with AD, 12 with vascular dementia (VaD), 14 with mixed dementia (MD), 24 with other dementia (OD) including Parkinson's disease dementia, frontotemporal dementia, paralytic dementia and 35 cognitively normal controls. The total plasma level of sRAGE was determined using sandwich ELISA method. Results : sRAGE concentration in AD is significantly decreased compared with healthy controls. However, the receiver operating characteristic curve analysis of sRAGE between the AD and the control shows a low diagnostic accuracy. Conclusions : Our results demonstrate that sRAGE may assist the diagnosis of AD from normal individuals, but cannot differentiate AD from VaD, MD or OD.